A mild route of synthesis metal/carbon novel core/shell nanospheres in ethanol system - Wang, Haibo; Jin, Quan; Yang, Lufeng; Liu, Yingliang (Journal of nanoparticle research : an interdisciplinary forum for nanoscale science and technology, 2013)
Precious metals core/shell nanospheres were synthesized via a one-pot method, we investigate a new route using 2,4-dihydroxybenzoic acid and formaldehyde served as carbonaceous shell, ethanol reducing metal particles served as core and l -lysine initiating to obtain core/shell structures. This synthesis was reflux in ethanol system at a low temperature of 80°. Uniform size, homogeneous morphology, and high purity of the product were synthesized by this method. Moreover, shell thickness are tunable when we change the dosage of metal and PVP ( l -lysine). The core/shell nanoparticles have the core diameter of 8–12 nm and the sphere shell diameter of 100–140 nm. Ag@C, Au@C, and Pd@C were prepared via the same method. The different dosage of PVP and sequence of formaldehyde are investigated in order to clarify the reaction mechanism. Based on this, we give a reasonable explanation to the universal method. TEM, XRD, FTIR, UV-spectra, and EDS (HRTEM) were used to characterize the core/shell nanostructures.